“Simpati: Siap mencegah Penyakit Hipertensi” di Kelurahan Kebon Waru Kota Bandung - Setiawan, Shellita Melanie Astuti; Wardhana, Yodi; Pura, Intan Salsabila; Karyana, Mey Meylani; Shafira, Dinda Adhita; Allatif, Denden; Lestari, Nabila Zahra (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Hypertension is known as " a silent killer. This research aims to increase the coverage of hypertension services; reduce the gap in hypertension services; increase the knowledge, skills, and methods of controlling cadres regarding hypertension; and produce educational media about hypertension in the form of video flip sheets and plates. T/ SIMPATI Nutrition Plate. Methodology: Conducting counseling and presentation of material packaged into workshops and training regarding procedures for counseling hypertension patients for 16 cadres in the Kebon Waru sub-district, and then carrying out Pre-test and Post-test activities to determine cadres' understanding of the material provided, as well as providing a feedback sheet regarding how to counsel hypertension. Results: From the results of the pre-test given to 16 cadres, the majority scored 70, while the post-test score was 90. The average post-test score of the participants increased by 8.75 from the average pre-test score. With the counseling results, the percentage of participants who passed was 75% and the percentage of participants who did not pass was 25%. Limitations: Limitations in this research include the number of respondents, the research object is only focused on cadres, and in the data collection process, such as the honesty factor in filling out the pre-test and post-test. Contribution: The results of this research are expected to provide information as a basis for preventing and increasing coverage of hypertension services.